2011
DOI: 10.1016/j.ajog.2011.02.049
|View full text |Cite
|
Sign up to set email alerts
|

Maternal/fetal mortality and fetal growth restriction: role of nitric oxide and virulence factors in intrauterine infection in rats

Abstract: Objective-The mechanism of infection-related mortality of pregnant rats and the intrauterine growth restriction (IUGR) are not understood. We assessed if nitric oxide (NO) has differential effects on infection with E. coli Dr/Afa mutants lacking either AfaE or AfaD invasins.Material and Methods-Sprague-Dawley rats were intrauterinally infected with the clinical strain of E. coli AfaE + D + or one of its isogenic mutants in the presence or absence of the NO synthesis inhibitor N G -nitro-L-arginine methyl ester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Comparing LPS responder (C3H/HeN) and nonresponder (C3H/HeJ) mice and Dr adhesin-positive E. coli and P fimbria-positive E. coli infections, Nowicki et al (403) observed that the infection level in the Dr-positive E. coli-infected C3H/HeN group treated with an inhibitor of NO, nitro-L-arginine methyl ester (L-NAME), was about 100-fold higher than that in the P adhesin-positive E. coli-infected, L-NAME-treated group. Dr adhesin-positive E. coli infection in mice (403) and AfaE/AfaD adhesin subunit-positive E. coli infection in rats (404) are followed by complications in pregnancy and death. Moreover, the death rate was increased by treatment with the NO blocker L-NAME in both mice and rat (403,404).…”
Section: Pregnancy Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing LPS responder (C3H/HeN) and nonresponder (C3H/HeJ) mice and Dr adhesin-positive E. coli and P fimbria-positive E. coli infections, Nowicki et al (403) observed that the infection level in the Dr-positive E. coli-infected C3H/HeN group treated with an inhibitor of NO, nitro-L-arginine methyl ester (L-NAME), was about 100-fold higher than that in the P adhesin-positive E. coli-infected, L-NAME-treated group. Dr adhesin-positive E. coli infection in mice (403) and AfaE/AfaD adhesin subunit-positive E. coli infection in rats (404) are followed by complications in pregnancy and death. Moreover, the death rate was increased by treatment with the NO blocker L-NAME in both mice and rat (403,404).…”
Section: Pregnancy Complicationsmentioning
confidence: 99%
“…Dr adhesin-positive E. coli infection in mice (403) and AfaE/AfaD adhesin subunit-positive E. coli infection in rats (404) are followed by complications in pregnancy and death. Moreover, the death rate was increased by treatment with the NO blocker L-NAME in both mice and rat (403,404). As indicated above for Dr adhesininduced pyelonephritis in the mouse model, the role of the mouse DAF in Dr adhesin-induced complications during pregnancy in the rat model is intriguing, considering that the rodent DAF is clearly not recognized by Afa/Dr adhesins (254).…”
Section: Pregnancy Complicationsmentioning
confidence: 99%
“…A subset of the cohort in the same study also exhibited an abundance of Peptostreptococcus anaerobius and associated shorter term pregnancies and newborns with lower length for age Z-score [ 159 ]. A study using pregnant rats showed that the weights of placenta and the offspring from rats infected with Escherichia coli (observed as a co-colonizer with Lactobacilli ) were significantly lower as compared to the non-infected controls [ 160 ]. Bacterial dysbiosis in the lower genital tract of pregnant females commonly results in bacterial vaginosis.…”
Section: Introduction: Infections In Pregnancy and The Developing Fetusmentioning
confidence: 99%
“…2 In addition to N 2 O, other ADHD risk factors could also influence NO synthesis in both mother and fetus. 6 9 For example, the endothelial nitric oxide synthase (eNOS) activity in fetal umbilical veins decreased by 40% during exposure to maternal smoking. 6 Moreover, chronic alcohol decreased uterine arterial eNOS expression and altered its activated state that is characterized by multisite phosphorylation.…”
mentioning
confidence: 99%